Lebanon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
Lebanon's credit growth in 2008-10 has been concentrated in trade and services, household loans, and the construction sector. These sectors accounted for almost 80 percent of all new loans extended since 2008. Real estate lending in particular has been increased substantially. On the demand side, a renewal in confidence following an improved political environment in 2008 led to a rebound in economic activity that, together with a real estate boom, fueled credit demand.